ЎҚУВЧИЛАРНИНГ ФИЗИКАГА ОИД КОМПЕТЕНЦИЯЛАРИНИ РИВОЖЛАНТИРИШДА МОБИЛ ДАСТУРИЙ ВОСИТАЛАРДАН ФОЙДАЛАНИШ - Жамолова, Ш.; Жўраев, Ҳ. (SCIENCE and SOCIETY, 2021)
This article discusses information about mobile programs, their role in organizing the educational process, the possibility of using mobile devices based on methodological foundations of teaching subjects, using mobile software in developing students’ competencies in physics.